PENJADWALAN FLOW SHOP MENGGUNAKAN PENDEKATAN CROSS ENTROPY-GENETIC ALGORITHM UNTUK MEMINIMASI MAKESPAN DI PT. XYZ - Arnan Jinawi; Budi Santoso; Tutuk Safirin (UPN Veteran Jawa Timur, 2022)
ABSTRACT Pandemic era is obviously forcing every elements of society, especially the industrial sectors, to adapt into the current situation. PT. XYZ is one of it that operate the flow shop packaging industry. Such as other industry, this industry had to restrict amount of employees that cause some certain change to the production scheduling. To operate it’s processess, this industry has to provide a schedule to minimize the makespan. This research is done to compare a LPT method used by the industry and CEGA method. CEGA method used to sequence any job due to its priority to be done sequentially. CEGA provide better maksepan that is 129,621 hours or 15,51% different to the current method. This method would save 20,13 hours or more efficeint 13,44% by the method used in prior method. CEGA method is ran with Matlab to support any optimal calculation done.